Amaqghira as a dancer, singer and drummer - Benjamin Obeghare Izu; Alethea de Villiers (Accelerando: BJMD, 2023)
Amagqirha have primarily been viewed and discussed in relation to divination and traditional healing practices. There have been very few studies on their involvement beyond healing. In order to address that gap, this paper explores the artistic aspect of amagqirha. The thesis of this work is that by concentrating on the amagqirha ritual space, which entails singing, dancing, drumming, and divination, we may unveil the artistic nature or prowess of amagqirha practices while recreating the significance of traditional healers in modern societies. Using informal discussions, interviews, and participant observation during amagqirha ceremonies in the townships of Motherwell, Gqeberha in the Eastern Cape and Rosemore, George in the Western Cape, this paper argues that amagqirha are not only diviners and healers but also great dancers, singers, and drummers, drawing heavily on indigenous knowledge inculcated in them during initiation rites and rituals.